Knowledge, Attitude and Practices Among Medical Students And Their Family Members Towards The COVID-19 Pandemic: An Online Based Cross-Sectional Study (KYAMC Journal, 2021)
Background: COVID-19 is an emerging infectious disease which has created a global health emergency status. It is now super spreading in the community of Bangladeshi population causing morbidity and mortality amongst masses.Objectives: The aim of this study is to find out the knowledge, attitude and practices of medical college students and their family members towards the Covid-19.Materials & Methods: This online cross sectional study was conducted from the 15 April to 30 April 2020 during the lockdown period in Bangladesh. Collected data was analyzed by using SPSS IBM version 22.0.Results: A total of 517 responses were obtained. The majority of the population 326 (63.06%) were female and 352 (68.09%) belonged to an age group of 21-30 years. This study has revealed that 412(79.69%) believe COVID-19 affect all age group, 311(60.15%) thinks that it affect the elder people seriously, 215(41.59%) thinks specific treatment is not available for COBID-19, Greater part of respondents 256(49.52%) says COVID-19 infection is preventable, 452(87.43%) gives positive opinion about government lockdown to avoid further spread of infection and 402(77.76%) believes physical distancing is helpful to prevent spread of this disease. Regarding 14 days quarantine period 375(72.53%) give positive answer, 425(82.20%) says COVID-19 affects world economy badly, 298(57.64%) thinks the situation may be controlled soon.Conclusion: Since prevention is better that cure, hence an increasing need of awareness amongst the local population regarding COVID-19 is required. Further extensive survey studies are required in future that can provide supportive data in developing and implementing public health policies regarding COVID-19 pandemic in our country.KYAMC Journal Vol. 11, No.-4, January 2021, Page 166-170